SENSUS PENDUDUK DI INDONESIA - Tukiran Tukiran (Pusat Studi Kependudukan dan Kebijakan, Universitas Gadjah Mada, 2000)
Although the population registration in Indonesia has long been put through, the result is still unreliable, thus population census should be considered as a major source in providing data of population and households. Since its independent status, Indonesia has carried out the census for five times: in 1961, 1971, 1980, 1990, and in 2000 with the goals of providing a considerable amount of details of population data such as: buildings and households, villages potential (potensi desa or podes), and main pattern frames for survey and others census applications.The collected data contain information of households and individuals by the census taking system both de jure and de facto for the entire population of Indonesia, including those living abroads such as diplomatic corps with their family members. For the 2000 population census of Indonesia or SP 2000, the data of household and population by temporary residence status, have been put through by the national Central Bureau of Statistic, whereas the data of those by permanent residence status have been carried out by the Regional Central Bureau of Statistic, which are all predicted would be finished before the end of the year of 2000.